Design And Tradeoff Characterizations Of High Frequency Balanced Amplifier For RF Integrated System - Tai, Wen Qi (Universiti Sains Malaysia, 2005)
This report included design, analysis and implementation of high frequency balanced amplifier operate at center frequency of 1.9 GHz. System and circuit design are carried out with the aid of a powerful design tool - Agilent’s Advanced Design System (ADS 2003A). Balanced amplifier is a type of amplifier that combines 2 similar single-ended amplifiers into single unit, which can perform amplification of input RF signal. There are two common types of single-ended amplifier: amplifier with lumped element and microstrip matching network. In this project, both types of amplifier are designed and built. Analysis and comparison carried out on this two different topology are included in this report. Initial design using ideal component provided the basic structure and complete circuit of the amplifiers. In the beginning stage, the design steps included mathematical calculations and analysis. Detailed design steps with replaced actual model are carried out after the structure of circuits are obtained. Different types of simulation using ADS are done to observe performances of the balanced amplifiers. Using features of ADS, the values of design are optimized to obtain required performances. Result of simulations are included in this report. The balanced amplifier design are implemented in both software and hardware. Circuit’s layout design using ADS’s features is part of hardware implementations. The amplifier circuits are built on printed circuit board (PCB). The hardwares built are tested with network and spectrum analyzer in to obtain required characteristics and specifications. Measurements taken from hardware test are compared to results from simulations. Variations that existed from both results are discussed in this report.